Monitoring of pesticide residues in crops irrigated with reclaimed water by a multiresidue method based on modified QuEChERS. Issue 36 (26th August 2021) - Martínez Bueno, M. J.; García Valverde, M.; Gómez-Ramos, M. M.; Valverde, A.; Martínez Galera, M.; Fernández-Alba, A. R.
Abstract : In this study, we aimed to validate a quick and easy extraction method for the simultaneous determination of 27 pesticide residues at trace levels in agricultural samples to monitor the presence of these contaminants released from reclaimed water. Abstract : In this study, we aimed to validate and apply a quick and easy extraction method for the simultaneous determination of 27 pesticide residues at trace levels in agricultural samples (soil, fruit, and leaf) to monitor the presence of these contaminants released from reclaimed water. The procedure was based on a salting-out extraction method with acidified acetonitrile, followed by a dispersive solid-phase extraction (d-SPE) clean-up step applying the C18 sorbent. Ultra-performance liquid chromatography coupled with electrospray tandem mass spectrometry (LC-MS/MS) was used for identification and quantification of the target analytes. This methodology provided recovery values higher than 70%, for all pesticides and matrices evaluated in the study, except for propamocarb in soil samples (35%). Repeatability and reproducibility results, calculated as relative standard deviations (RSD, %), ranged between 1% and 18% in both cases. No remarkable matrix effects were observed for vegetable samples, except for thiamethoxam in red cabbage, and hexythiazox in carrot and leaves (between 30 and 40%). Soil samples showed a moderate matrix effect (between 21 and 35%) for more than 80% of the compounds. Monitoring pesticide residues found in agricultural samples irrigated with contaminated reclaimed water under controlled conditions revealed the efficacy of the proposed method. Three common vegetables were grown to evaluate the different migration and distribution rates in crops and soil. Pesticide accumulation in the different parts of the crop (soil, fruit, and leaves) and the potential human exposure to pesticides through daily intake were also discussed.